Pola Konsumsi Minuman Ringan (Soft Drink) Terhadap Status Gizi Mahasiswa Universitas Muhammadiyah Parepare - Musyahida; Dewi Mutia; Nurhasanah (Jurnal Bidan Cendrawasih Palu, 2020)
Soft drinks can cause weight gain and risk of obesity so that it can potentially cause type 2 diabetes mellitus, cancer, heart attack, and stroke. The purpose of this study was to determine the pattern of consumption of soft drinks with the nutritional status of Muhammadiyah Parepare University Students. This research method is an observational analytic study with a cross sectional study design. The sample in this study was 99 respondents with proportional sampling technique of collecting data through interviews that refer to the questionnaire and direct observation. Data analysis using SPSS version 24 with chi square test presented in tabular and narrative form. The results of this study indicate that there is an influence of soft drink consumption patterns on the nutritional status of University of Muhammadiyah Parepare students by using the chi square test with a value of p (value) h = 0,000. It is expected that students should pay attention to the type of drink and reduce the daily consumption of soft drinks to avoid under- or over-nutrition status.